The Influence of Service Quality on Customer Satisfaction at the Bakso Semar Restaurant in Bandung - Mila Rachmawati; Nandan Limakrisna; Boyke Setiawan Soeratin; Andriasan Sudarso; Udin Ahidin (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this study is to identify the aspects of service quality at the Bandung restaurant Bakso Semar that have an impact on patron satisfaction. A sample of fifty respondents who had made purchases at Bandung restaurants was employed in this study. In this study, basic linear analysis along with quantitative analytic approaches were used. Validity, reliability, correlation analysis, simple linear regression analysis, outcomes of linear regression analysis, and determination tests were the statistical tests performed in this study. The results of validity and reliability tests demonstrated the validity and reliability of the research's questionnaire. The findings of the correlation coefficient test indicate a modest degree of link between customer satisfaction and service quality. It was discovered by the outcomes of the linear regression analysis that customer happiness is influenced by service quality. The findings of the determination test indicated that, of the variables included in this study, other factors affected the remaining 52.0% of the relationship between service quality and customer happiness.